Millets (Kshudra Dhanya): Nurturing Health And Preventing Lifestyle Disorders (AYUSHDHARA, 2024)
Ayurveda is based on the theory of Trayo-Upsatamba i.e., which refers to the pillars of Ayurveda: Ahara (diet), Nidra (sleep) and Bramhcharya. The key to adhering the first principal of Ayurveda, Swasthasya Swasthya Raksham (to sustain a healthy life), is Ahara (nutritious food), or we can say that balanced diet. WHO has declared 2023 “International Year of Millets” with the theme “Harnessing the untapped potential of millets for food security, nutrition, and sustainable agriculture’’. According to Ayurveda, keeping healthy eating habits can regulate and avoid all ailments. In Ayurveda different Acharya have specified various type of Aahar varga. Millets are described under Kudhanya of Bhavparkash Dhanyavarga (category of cereals). Kshudra dhanya (millets) is a group of small seeded cereals used by humans by ages. Millets (Kshudra dhanya) are drought resistant, serves as a good source of proteins, micronutrient, phytochemicals and gluten free. Due to an imbalance diet of high-calorie, fast foods, there are issues with health that must be resolved on a global scale. The so-called general diseases of present day include obesity, diabetes, cardiac arrest, porous bones and depression etc. This attempt at a review of Kshudra dhanya may be helpful to understand their complete health benefits for daily lifestyle disorders and for balancing the disease condition as well.